SOCIOCULTURAL APPROACH TO TEACHING RUSSIAN AS A FOREIGN LANGUAGE (TAMADDUN NURI JURNALI, 2024)
The article examines the socio-cultural approach as a methodological basis in teaching Russian as a foreign language. Particular attention is paid to the integration of language training with introducing students to cultural values ​​and traditions of the Russian people. It is emphasized that this approach contributes to the development of communication skills. The socio-cultural approach is considered as an effective tool for the formation of a harmonious, socially adapted personality, ready to interact in a global society.